SOUNDTRACK LA TABKI YA ṢAGHIRĪ DALAM FILM ABṬALU DĪGITAL (Analisis Semiotik Riffaterre) - Firdausah, Isyqie (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
This research has “Lā Tabki yā Ṣaghīrī” as a material object, an original soundtrack of Abṭalu Dīgital, a very popular movie in s2000. The song lyric is analyzed by Riffaterre’s Semiotics Theory which introduces two levels of reading.  Based on the analysis of this research, the potential hypogram shows that the parents give advices about reaching for dreams to their child who is in despair. The dream has something to do with raindrops philosophy. The models found are juhdun ‘effort’, amal ‘dream’, alwān ‘colours’, dan hayāh ‘life’. The matrix is “advises about human as khalifatullah in the world”. The actual hypogram is human’s missions as khalifatullah based on verses of al-Quran, hadith of the prophet, and interpretations of some mufassir such as Quraish Shihab and al-Buthi. It then is concluded that khalifah is like raindrop. It emits various colour spectrums, shows beautiful rainbow, and spreads-out love. One raindrop collaborates to another and sticks together to become pulse of the world.